Effects of walking speed on magnitude and symmetry of ground reaction forces in individuals with transfemoral prosthesis. (January 2022) - Kobayashi, Toshiki; Hu, Mingyu; Amma, Ryo; Hisano, Genki; Murata, Hiroto; Ichimura, Daisuke; Hobara, Hiroaki
Abstract: Individuals with unilateral transfemoral amputation (uTFA) walk asymmetrically. Investigating gait symmetry in ground reaction force (GRF) is critical because asymmetric loading on the residual limb can result in injury. The aim of this study was to investigate the GRF of individuals with uTFA by systematically controlling their walking at eight speeds (2.0–5.5 km/h with increments of 0.5 km/h) on a treadmill. Forty-eight individuals participated in this study, which included 24 individuals with uTFA (K3 and K4) and 24 individuals without amputation. GRFs (anteroposterior, mediolateral, and vertical) of the prosthetic and intact limb steps were collected for the individuals with uTFA and those of the right limb were collected for the control group. Peak force values of the GRF components, temporal parameters, impulses, and their asymmetry ratios were investigated and statistically analyzed. With an increasing walking speed, the magnitude of GRF changed gradually; individuals with uTFA exhibited increased GRF asymmetry in the vertical and mediolateral components, while that of the anteroposterior component remained constant. uTFA individuals typically maintained a constant asymmetry ratio in the mediolateral and anteroposterior (braking and propulsive) GRF impulses across a wide range of walking speeds. This result suggests that individuals with uTFA may cope with various walking speeds by maintaining symmetric mediolateral and anteroposterior impulses. The data provided in this study can serve as normative data for the GRF and its symmetry across a range of walking speeds in individuals with uTFA.